Analisis Perubahan Perilaku Konsumen dalam Konteks Bisnis Elektronik Pasca-Pandemi COVID-19: Implikasi dan Strategi Pengembangan Bisnis - Gunawan, Achmad Rezky; Amali, Amali; Kurniawan, Jidan Restu; Saepul, Muhammad; Rifa'i, Anggi Muhammad (Universitas Pelita Bangsa, 2024)
The COVID-19 pandemic has changed the global business environment significantly, especially in the electronics and e-commerce industries. In this context, consumer behavior has changed dramatically, with a significant increase in online purchases and a preference for brands that offer exceptional digital experiences. The impact of these changes is significant for e-commerce companies, which must adapt their strategies to remain relevant and competitive in an increasingly digital and online marketplace. This analysis focuses on factors that influence changes in consumer behavior, including: Changing purchasing preferences, improving online security and privacy, and seeking better digital experiences. In addition, we discuss business development strategies that can help companies face challenges, such as increasing investment in technology infrastructure, developing marketing strategies that focus on customer experience, and improving data security and privacy. By understanding the dynamics of changing consumer behavior post-pandemic, the business world can take the right steps to position themselves effectively in this growing market and strengthen their competitiveness in the digital business era.